Pengembangan Eduwisata Petualangan Alam (Adventure) di Situs Pati Ayam Kudus - Noor Janah; Fauziyatus SM; Frisilia Febriyanti; Didi Nur Jamaludin (Education Mind Based Development Association, 2021)
Patiayam Kudus Archaeological Site is a site that contains ancient historical relics found around Mount Patiayam. This research is a phenomenological research with a qualitative approach. The subjects of this study were determined by purposive sampling. Data techniques include observation, interviews, and documentation. In the beginning, the people of Terban Kudus Village developed tourism in the Patiayam Archaeological Site area by presenting the house as a tourist destination, then the local community took the initiative to introduce the Patiayam Site widely and more attractive by presenting the educational-based Patiayam Advanture on the Patiayam Site. Tourists who use the Patiayam Advanture services can go on an adventure with various facilities services such as an Offroad Jeep car as well as lodging services. This can be an interesting adventure to bring tourists to know ancient objects such as the Patiayam Archaeological Museum, Gardu Pandang, Sendang Pengilon and Patiayam Cave.